BROKEN & UNEQUAL: THE SOUTH AFRICAN EDUCATION SYSTEM AND THE ATTAINMENT OF THE RIGHT TO BASIC EDUCATION THROUGH LITIGATION (The Pretoria Student Law Review, 2021)
In 1994, South Africa transitioned into a new democratic and constitutional society. Since then, the South African Constitutionnecessitates the transformation of the public basic education system. A new public education system aimed at addressing the malaise of the past. To this end, South African jurisprudence recognises the right to basic education as a right that must be (i) equally accessible to all and (ii) immediately realisable without delay. However, the new education system has not completely succeeded in eliminating the legacy of apartheid, and there are residual differences and polarisation on various grounds, such as race and/or class. Accordingly, this article concedes that a critical survey of South African jurisprudence on the realisation of the right to basic education reveals that there are problems in the delivery of the right to basic education in South Africa. This is particularly the case in relation to black and/or poor South African pupils in the public education system. As such, the article intends to show that litigation (or the threat thereto), plays a fundamental role in the realisation and fulfilment of the right to basic education in South Africa.
Keywords: basic education; immediately recognisable rights; public education system; equal accessibility; socio-economic rights